Analysis of Factors Affecting Stock Prices in Food And Beverage Companies Listed on the Indonesia Stock Exchange - Yousita Abigail Lesnussa; Aprina Wati; Fera; Julia Monik Nasution; Tika Meisin br Sinulingga; Ribka Sari Butar-Butar (Institute of Computer Science (IOCS), 2022)
This research has the aim to test the truth of Return On Equity (ROE), Earning Per Share (EPS), and Net Profit Margin (NPM) giving a simultaneous or partial effect on stock prices. In this research, the value of the company/company is proxied using Price to Book Value (PBV). This research uses a population of 25 Food and Beverage companies on the IDX list during the 2018-2020 period. Materials/data for the acquisition test are sourced from the financial report notes issued by the IDX. The sampling procedure uses a purposive sampling method that only uses Food and Beverage companies that are listed in succession during the 2018-2020 period, publishes historical stock prices during the research period, and does not experience losses during the research period. The number of samples that passed the category was 17 Food and Beverage companies which were studied for 3 years so the observation data were 51 observations. The results of the Coefficient of Determination in this study, which can be observed in Adjusted R Square, have a score of 79.8%. Stock prices can be influenced by ROE, EPS, and NPM, while the remaining 20.2% are influenced by other aspects that are not included in the study.